2021
DOI: 10.1002/hyp.14406
|View full text |Cite
|
Sign up to set email alerts
|

Isotopic analysis to quantify the role of the Indian monsoon on water resources of selected river basins in the Himalayas

Abstract: Western disturbances (WDs) and Indian summer monsoon (ISM) led precipitation play a central role in the Himalayan water budget. Estimating their contributions to water resource is although a challenging but essential for hydrologic understanding and effective water resource management. In this study, we used stable water isotope data of precipitation and surface waters to estimate the contribution of ISM and WDs to the water resources in three mountainous river basins ‐ Indus, Bhagirathi and Teesta river basin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 112 publications
(189 reference statements)
0
1
0
Order By: Relevance
“…The relative contribution of glaciers and snow to the spring meltwater is highly sensitive to location: analysing δ 18 O and δ 2 H in the Sutri Dhaka Glacier Basin in the Western Himalaya, Singh et al (2019a) found that downstream river discharge there comprised 80% icemelt and 20% snowmelt. Recent isotopic analysis has estimated that 70% of all water discharged by the Indus river comes from precipitation associated with WDs (Jeelani et al, 2021). Similar contributions have been found for other basins in the northwest Himalaya (Lone et al, 2022a;Nabi et al, 2023).…”
Section: Water Supplysupporting
confidence: 54%
“…The relative contribution of glaciers and snow to the spring meltwater is highly sensitive to location: analysing δ 18 O and δ 2 H in the Sutri Dhaka Glacier Basin in the Western Himalaya, Singh et al (2019a) found that downstream river discharge there comprised 80% icemelt and 20% snowmelt. Recent isotopic analysis has estimated that 70% of all water discharged by the Indus river comes from precipitation associated with WDs (Jeelani et al, 2021). Similar contributions have been found for other basins in the northwest Himalaya (Lone et al, 2022a;Nabi et al, 2023).…”
Section: Water Supplysupporting
confidence: 54%
“…The spatial and temporal variations in the δD and δ 18 O in rivers in arid watersheds can be driven by precipitation (ultimate source of river water) that varies by season and by isotopic enrichment from evaporation (Stewart, 1975;Simpson and Herczeg, 1991;Clark and Fritz, 1997;Huang and Pang, 2012;Chen and Tian, 2021;Jeelani et al, 2021). Conversely, the temporal variations in TDI concentrations can be driven by ET-induced chemical changes in the water column, water-rock interactions, or hydrological transport of solutes from the watershed to the river (Ramatlapeng et al, 2021).…”
Section: Evidence Of Evaporation From the Stable Isotopic Composition...mentioning
confidence: 99%